2014
DOI: 10.1007/s10152-014-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

CO2-induced fertilization impairment in Strongylocentrotus droebachiensis collected in the Arctic

Abstract: Fertilization depends on distribution and aggregation patterns of sea urchins which influence gamete contact time and may potentially enhance their vulnerability to ocean acidification. In this study, we conducted fertilization experiments to assess the effects of selected pH scenarios on fertilization success of Strongylocentrotus droebachiensis, from Spitsbergen, Arctic. Acidification was achieved by aerating seawater with different CO 2 partial pressures to represent preindustrial and present conditions (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…These impacts are likely species-and population-specific, with some urchins exhibiting no impact of low pH on egg jelly coat area, and populations exhibiting varied impacts depending on prior pH exposure (Foo et al, 2018). Egg intracellular pH adjusts according to the external chemical environment (Ciapa and Philippe, 2013;Bögner et al, 2014), which may also hamper egg activation by interfering with calcium signaling and actin dynamics (Limatola et al, 2020). Indeed, Shi et al (2017b) observed that low pH disrupts the intracellular calcium ion (Ca 2+ ) activity in T. granosa eggs, which was associated with reduced fertilization rates.…”
Section: Gamete Mechanisms That Influence Fertilization Ratementioning
confidence: 99%
“…These impacts are likely species-and population-specific, with some urchins exhibiting no impact of low pH on egg jelly coat area, and populations exhibiting varied impacts depending on prior pH exposure (Foo et al, 2018). Egg intracellular pH adjusts according to the external chemical environment (Ciapa and Philippe, 2013;Bögner et al, 2014), which may also hamper egg activation by interfering with calcium signaling and actin dynamics (Limatola et al, 2020). Indeed, Shi et al (2017b) observed that low pH disrupts the intracellular calcium ion (Ca 2+ ) activity in T. granosa eggs, which was associated with reduced fertilization rates.…”
Section: Gamete Mechanisms That Influence Fertilization Ratementioning
confidence: 99%
“…More evidence of the negative effects of decreasing pH on fertilization success of invertebrates has been found (Sewell et al, 2013;Bögner et al, 2014;Frieder, 2014;Scanes et al, 2014;Sung et al, 2014) and RCP8.5 acidification has been shown to have negative effects on clam larval dispersal (Clements and Hunt, 2014).…”
Section: Updates To Ar5mentioning
confidence: 99%
“…Interestingly, Ciapa and Philippe [112] found eggs showing cellular constrictions and nuclear envelope breakdown, probably related to alterations in the Ca i 2+ regulation under cytosolic acidosis caused by the Na + deprivation outside the cell, followed by compensation throughout additional removal of HCO 3f rom the media. Constricted eggs which failed to progress into the cell cycle were also observed by Bögner, et al [22]. For the accomplishment of cytokinesis a highly-regulated sequence of events concerning the nucleus and the cytosol must occur and the communication between these compartments is essential.…”
Section: Evidence Of Subcellular Alterations Due To Ocean Acidification Exposurementioning
confidence: 67%
“…Fertilization rate óó Proportion of fertilized eggs [22,23] ó Fecundity (reversible effect) [24] ó Fertilization success at longer exposure periods before fertilization [25] ò Polyspermy rates [26] Depending on species origin and methods used, there are inconsistent results indicating the need of a standard protocol.…”
Section: Stage Studied Effect [Reference] Observationsmentioning
confidence: 99%
See 1 more Smart Citation